A saúde bucal no município de Franca (SP): da assistência ao perfil profissional dos cirurgiões-dentistas - Aguila, Andréa Porto (2009)
The oral health is, without a doubt, integrant part of the health human being, and started to have a bigger importance as public politics in Brazil after the promulgation of the Federal Constitution of 1988 and the implantation of the Only System of Health. In this direction, the survey of the demands in oral health in the different territories can assist in the formularization of politics more effective for the cities. The objective of this work was to carry through a survey of the assistance in oral health in the Basic Units of Health of the Franca City of and characterizing the profile of the surgeon-dentists of the City department of Health of the Franca City (SP), in the year of 2007. Were used secondary data, collectede in bulletins of odontological production, supplied for the Coordination of Oral Health of the city; and information gotten through the answers of the surgeon-dentists to a questionnaire. In accordance with the gotten results, the covering of the consults in Oral Health of the city in 2007 was, on average, of 4,91%. The procedures are divided by age bands and the most realized had been the clinical ones (67,73%), followed for the actions of promotion and prevention of health (22,15%), surgical procedures (8, 91%), and procedures with disgnostic purpose (1,20%). Of the 44 surgeon-dentists of the municipal picture, 46,15% are men, who carry through 41,40% of the total of procedures, and 53,85% are women who carry through 58,60% remains. Was found a significant relation between the age band of the patients and the sex of the Professional (p< 0.01), being that, professionals of the feminine sex take care of more frequently patient of low ages. Professionals of the masculine sex have preference for the surgical procedures (p< 0.001). Among the told specialties they are distinguished it Collective Public Health/, Health of the Family and Promotion of Health (52.22%). With exception of the professionals with Specialization in Dentística, the clinical procedures significantly had been carried through (p< 0.01) by all the Specialties.